2014
DOI: 10.1002/gcc.22162
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the ATM‐CHEK2‐BRCA1 axis determine genetic predisposition and clinical presentation of papillary thyroid carcinoma

Abstract: The risk of developing papillary thyroid carcinoma (PTC), the most frequent form of thyroid malignancy, is elevated up to 8.6-fold in first-degree relatives of PTC patients. The familial risk could be explained by high-penetrance mutations in yet unidentified genes, or polygenic action of low-penetrance alleles. Since the DNA-damaging exposure to ionizing radiation is a known risk factor for thyroid cancer, polymorphisms in DNA repair genes are likely to affect this risk. In a search for low-penetrance suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 39 publications
4
35
1
Order By: Relevance
“…The odds ratio for breast carcinoma given the I157T mutation was 1.5 in Poland, 1.4 for the Finnish population, 3.6 in the German population and 4.5 in the Byelorussian population [ 16 ],[ 17 ],[ 37 ]. Our results confirmed also recently published research from another region of Poland (central Poland) conducted on a large group of patients with papillary thyroid cancer, which showed OR = 2.2 (p = 2.37 −10 ) [ 38 ].…”
Section: Resultssupporting
confidence: 92%
“…The odds ratio for breast carcinoma given the I157T mutation was 1.5 in Poland, 1.4 for the Finnish population, 3.6 in the German population and 4.5 in the Byelorussian population [ 16 ],[ 17 ],[ 37 ]. Our results confirmed also recently published research from another region of Poland (central Poland) conducted on a large group of patients with papillary thyroid cancer, which showed OR = 2.2 (p = 2.37 −10 ) [ 38 ].…”
Section: Resultssupporting
confidence: 92%
“…Based on these data, it was difficult to figure out how this single polymorphism might be associated with a decreased cancer risk for individuals who were exposed to radiation. Instead, a gene-gene interaction of the ATM gene with BRCA1 has been reported [28, 52]. Therefore, it could be expected that the polygenic action of unidentified alleles or genes probably played a non-negligible role on the function of the rs1801516 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that this conserved variant falling just upstream of the FAT kinase domain [ 23 ] may modify the genetic susceptibility to DTC and its clinical manifestation in carriers of a rare BRCA1 pathogenic variant. In particular, both ATM rs1801516 and BRCA1 rs16941 variants modify the impact of male gender on clinical variables [ 24 ]. An emerging hypothesis is that ATM is exploited in undamaged cells in other signalling pathways that DSBs repair in response to various stimuli or physiological situations such as hormonal exposure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%